Juicios y sentencias del Tribunal de la Santa Inquisición de Murcia contra ciudadanos residentes en la Corona de Aragón, desde el siglo XV al XIX. - VILLA, RAMÓN DOMÉNECH (Scripta, 2020)
For five centuries, this court was in charge of judging the most diverse cases and carrying out innumerable persecutions, with greater or less intensity and harshness, against those who departed from the repressive doctrine set by the church. Added to the alleged religious crimes against doctrine and faith were those of a sexual nature, in addition to those carried out against numerous clerics of questionable behavior and ethical and moral integrity. Extracted from the catalog published by Juan Bláquez Miguel in the Murgetana magazine in 1987, having as its main source the existing documentation in the National Historical Archive, the study that is presented analyzes the trials, sentences and dates that the institution of the cross, the sword and olive branch carried out against numerous citizens who, for one reason or another, were in territories belonging to the Crown of Aragon at the time of being arrested and tried for different reasons, some of them the most crazy that we can imagine today: Jews, Muslims, bigamists, married clergymen, witches, heretics, priest who made the most varied dihonest proposals for their position... all of them are part of the list that will occupy the following pages. Situations of the most varied and from which we cannot separate the most cruel sentences imaginable.